2003
DOI: 10.1259/dmfr/65139094
|View full text |Cite
|
Sign up to set email alerts
|

Conventional sinus radiography compared with CT in the diagnosis of acute sinusitis

Abstract: The sensitivity of plain film radiography for detecting sinus opacifications was unacceptably low for the ethmoid, frontal and sphenoid sinuses. The specificity was high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 4 publications
2
48
0
3
Order By: Relevance
“…[1][2][3] CT imaging adds valuable information to the clinical diagnosis of rhinosinusitis regarding the extent and severity of inflammation and exquisitely demonstrates anatomy and surgically relevant anatomic variants. Due to a typically younger patient population and the proximity of radiosensitive organs such as the eye lenses and thyroid gland, increased concern is focused on radiation dosage.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] CT imaging adds valuable information to the clinical diagnosis of rhinosinusitis regarding the extent and severity of inflammation and exquisitely demonstrates anatomy and surgically relevant anatomic variants. Due to a typically younger patient population and the proximity of radiosensitive organs such as the eye lenses and thyroid gland, increased concern is focused on radiation dosage.…”
Section: Discussionmentioning
confidence: 99%
“…This concept is particularly useful in developing countries where radiographs are still widely in use to confirm the diagnosis of CRS. [10][11][12] This study found postnasal dripping, nasal blockage and nasal congestion as the three most prevalent symptoms of CRS. This finding is similar to what was reported in similar studies by Ologe et al and Da Lilly-Tariah et al 22,23 The maxillary sinus was the most affected PNS with 91% of the maxillary sinuses studied having some form of abnormality (opacification).…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Based on this reality in environments like ours, it becomes imperative to ascertain the clinical merits in cost effective yet efficacious means of confirming the diagnosis of CRS, grading the disease and prioritizing treatment by combining plain radiograph scoring of a patients' disease with their overall symptom severity score. In rural areas where radiographic tools may not be available, questionnaire scoring of patients' symptoms can be an important predictor of the presence of lesion(s) on plain radiographs of the PNS.…”
mentioning
confidence: 99%
“…The radiation dose using CT can be performed with as low mAs (20 mAs) as possible due to the contrast of bone and air, and hence the dose will be almost equal to plain films (Aalokken, 2003;Hagtvedt, 2003). Though MR can demonstrate the anatomy, CT is superior to delineate the bony details, as well as depicting soft tissue masses, in addition the surgeons always use CT as a surgical map.…”
Section: Imaging Modalitiesmentioning
confidence: 99%